2016
DOI: 10.1073/pnas.1600739113
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-dependent compositional change in Mediator in ARF7- and ARF19-mediated transcription

Abstract: Mediator is a multiprotein complex that integrates the signals from transcription factors binding to the promoter and transmits them to achieve gene transcription. The subunits of Mediator complex reside in four modules: the head, middle, tail, and dissociable CDK8 kinase module (CKM). The head, middle, and tail modules form the core Mediator complex, and the association of CKM can modify the function of Mediator in transcription. Here, we show genetic and biochemical evidence that CKM-associated Mediator tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 45 publications
4
97
0
1
Order By: Relevance
“…The results of the present study also showed that the promoter region, at least 3 kb, of RSOsPR10 drives root‐specific gene expression in lateral root primordia and at the basal region of growing lateral roots (Figure ). Several other studies have suggested that JA and auxin signaling and their crosstalk are important in the formation and growth of lateral roots (Ito et al., ; Lu et al., ; Sun et al., ). Therefore, we hypothesize that RSOsPR10 is one of the key molecules in root development.…”
Section: Discussionmentioning
confidence: 98%
“…The results of the present study also showed that the promoter region, at least 3 kb, of RSOsPR10 drives root‐specific gene expression in lateral root primordia and at the basal region of growing lateral roots (Figure ). Several other studies have suggested that JA and auxin signaling and their crosstalk are important in the formation and growth of lateral roots (Ito et al., ; Lu et al., ; Sun et al., ). Therefore, we hypothesize that RSOsPR10 is one of the key molecules in root development.…”
Section: Discussionmentioning
confidence: 98%
“…TPL recruitment and its own multimerization could stabilize ARF-IAA interactions, which would explain why IAAs expressed without TPL fusions are poor repressors in yeast. It is also possible that binding of the IAA to the ARF could lead to conformational changes in the flexible middle region of the ARF that blocks recruitment of coactivators (33,39) or changes the module composition of core transcriptional machinery like the Mediator complex (40). Phosphorylation of the middle region in ARF7 and ARF19 has been shown to inhibit IAA interaction (41), indicating that signal integration from other pathways may take advantage of a link between an IAA interaction and the activity of the ARF middle region.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the middle region of ARF5 interacts with the SWI/SNF chromatin remodeling ATPases BRAMA and SPLAYED, possibly to reduce nucleosome occupancy and allow for the recruitment of transcription machinery (Wu et al., ). Additionally, ARF7 interacts with Mediator subunits, directly tethering transcriptional activation machinery to its binding sites in the chromosome (Ito et al., ). Class B and C ARF s are historically categorized as repressor ARF s, although the mechanism through which they confer repression has not been identified.…”
Section: Supplemental Analysesmentioning
confidence: 99%